Family and domestic violence leave review - Cassells, Rebecca; Duncan, Alan; Hailemariam, Abebe; Mavisakalyan, Astghik (2022)
The Bankwest Curtin Economics Centre was commissioned to undertake an independent economic analysis of the cost of providing paid family and domestic violence leave to workers on the modern award wage by the Australian Council of Trade Unions (ACTU), as part of the ACTU’s submission to the Fair Work Commission’s 2021 review of family and domestic violence leave.